Zusammenhänge zwischen Wetterlagenhäufigkeit und Niederschlagsverteilung im zentralmexikanischen Hochland, dargestellt am Beispiel des Hochbeckens von Puebla - Klaus, Dieter (ERDKUNDE, 1971)
High altitude weather maps (500 and 700 mb level), which exist for Mexico, the southern portion of the USA and the Gulf zone, were used to determine typical stream line structures and the frequency of their occurrence over the year for the Puebla high basin. These were correlated with the frequency of occurrence of precipitation of more than 0.1 mm on less than 25%, 25% to 65% and more than 65% respectively of the surface of the Puebla high basin. In addition, zones within the study area favoured by precipitation because of a particular type of circulation were determined and the basis of their dependence on weather and relief outlined. It could be shown that, in genetically identical precipitation areas, the annual sequence of monthly precipitation amounts was very similar for all observation stations and that the months with maximal precipitation amounts coincide with the months of maximum frequency of the type of circulation influencing the precipitation areas.